Risikoeinstellung und Risikowahrnehmung von Milchproduzenten in Österreich; Risk Attitude and Risk Perception of Dairy Farmers in Austria - Markus Scharner; Siegfried Poc̈htrager; Manuela Larcher (German Journal of Agricultural Economics (GJAE), 2016)
– Risk management measures to ensure successful strategic planning and long-term income stabilization are becoming increasingly important for agricultural enterprises. Dealing with risks and the willingness to pay for risk management measures are highly dependent on individual attitude towards and perception of risk. Against this background, the present paper examines the risk attitude and perception of Austrian farmers using dairy production as an example. The data consists of an online survey of 109 dairy producers. The results show that the producers' attitude - various psychological (self-assessment, business- related statements) and economic methods (Holt-and-Laury Lottery) were applied - is prevalent risk neutral. The measurement of subjective risk perception shows that Austrian dairy farmers are concerned with policy and market risks.
Keywords: 330